Pengaruh Keterikatan Karyawan (Employee Engagement), Otonomi Kerja (Job Autonomy), dan Kompensasi terhadap Kinerja Karyawan pada PT. XYZ - Agitia Maharani; Faldhi Fadilla Guci; Agung Priyono (Management and Leadership Study Programme, 2026)
This study aims to analyze the influence of employee engagement, job autonomy, and compensation policies on employee performance at PT. XYZ. The research was motivated by human resource issues such as employee tardiness, fluctuations in sales target achievement, and dissatisfaction with the company’s compensation system amid increasingly competitive conditions in the cosmetic industry. This study employed a quantitative approach with data collection conducted through questionnaires. The sampling technique used was saturated sampling with a total sample of 70 employees of PT. XYZ. Data analysis was carried out using Structural Equation Modeling–Partial Least Square (SEM-PLS). The results show that employee engagement has a positive and significant effect on employee performance, indicating that employees’ emotional attachment can increase loyalty, work enthusiasm, and responsibility. Job autonomy also has a positive and significant effect on employee performance because it provides flexibility in decision-making and work methods. In addition, compensation policies have a positive and significant effect on employee performance, where a fair and competitive compensation system can enhance employee motivation and productivity..